Comparative Analysis of Electrical Energy Potential from Coconut Dregs Biobriquettes Using the Pyrolysis Method with Biomass and Direct Burning Types - Sutanto, Bintang; Jelita, Marhama (Program Studi Teknik Elektro Universitas Khairun, 2024)
Riau is the province that produces the largest coconut in Indonesia, in 2019 coconut production in Riau reached 417,172.00 tons / year with coconut production of that amount producing a lot of waste as well, one of which was coconut pulp waste of 56,943 tons. If left alone, coconut pulp waste can have a negative impact on the environment. The purpose of this study is the use of coconut pulp waste as biobriquettes and the potential of electrical energy generated in Riau. The method of making biobriquettes uses the Pirolysis method with different types of combustion, namely biomass combustion and direct combustion, the results of this study are experiments conducted from 500 grams of coconut pulp to produce biobriquettes in biomass combustion which is 360 grams and in direct combustion of 240 grams. Characteristic testing is carried out manually, using biomass stoves and biobriquettes as fuel. Biomass combustion is obtained calorific value of 229.16 cal / gram, thermal efficiency of 7%, electrical energy conversion of 0.26655 kWh and electrical energy produced in Riau Province in 2019 which is 173,432,957.3 kWh. Meanwhile, direct combustion obtained a calorific value of 216.6 cal / gram, thermal efficiency of 6%, electrical energy conversion of 0.2518 and electrical energy in Riau province of 109,314,879.6 cal / gram. It can be concluded that biomass combustion is better than direct combustion.Â